Genetic Mechanism and Environment Implications of Siderites in the Lopingian Coal-Bearing Series, Western Guizhou of China: Constrained by Whole-Rock and In Situ Geochemistry - Yang, Tianyang; Shen, Yulin; Qin, Yong; Zhang, Yijie; Lu, Lu; Jin, Jun; Zhao, Yong; Zhu, Yulin; Zhang, Yunfei (Frontiers in Earth Science, 2021)
A large number of siderites have been found in the Lopingian (Late Permian) coal-bearing series in western Guizhou, which occurs in various microscopic morphologies and has potential insights into the sedimentary and diagenetic environments. An integrated set of analyses has been carried out to unravel the genetic mechanism of the siderites and their environmental implications. According to the microscopic morphology, the siderites can be generally divided into 3 types and 6 subtypes, including gelatinous siderites (I), microlite siderites (II1), powder crystal siderites (II2), petal-like siderite (III1), radiating fibrous siderite (III2), and concentric siderite (III3). Whole-rock geochemical results show that the iron source for the formation of the siderites was mainly from extensive weathering of the Emeishan high titanium basalts in hot climate conditions. The carbon and oxygen isotopic results indicate that the origin of CO2 in type I siderites is derived from the dehydroxylation of organic matter. The CO2 in type II1 and type II2 siderites is mainly derived from deposited organic matter and marine carbonate rocks, respectively. The CO2 source of type III siderites is sedimentary organic matter and marine carbonate rocks and is affected by different fluids during diagenesis. The whole-rock and in-situ geochemical characteristics further point to that type I siderites were formed in the synsedimentary period most strongly affected by seawater. Redox proxies such as V/Sc、V/(V+Ni) and δ Ce constrained their formation in a stable and weakly reduced condition. Type II siderites could have been developed in saltwater. Among them, type II1 siderites were formed in the early diagenetic stage, while type II2 siderites originated by recrystallization of type II1 siderites and accompanied by metasomatism with calcites under diagenetic fluids of weak reduction to weak oxidation conditions. Type III siderites were formed under the influence of multi-stage diagenetic fluids. Among them, Type III1 siderites formed by the growth of powder crystal siderites (II2) under diagenetic fluids with a weak reducing condition. Type III2 siderites formed by growth around microlite siderites under weak reducing diagenetic fluids. Type III3 siderites formed by concentric growth in diagenetic fluids with weak reduction to weak oxidation conditions and relatively active conditions.